Mapping Research on Digital Competencies in Science Education: A Bibliometric Analysis - Veraszto, Estefano Vizconde (2025)
This study maps the advancement of digital competencies in science education through a bibliometric analysis from 2005 to 2024. The development of digital competencies is crucial for science education in disciplines such as biology, chemistry, and physics, but the lack of technological infrastructure and inadequate teacher training hinder their integration. Artificial Intelligence (AI) emerges as a promising tool to enhance these competencies, facilitating adaptive and personalized learning environments. Using VOSviewer and SciMAT, 64 articles from the Web of Science were analyzed, identifying 393 keywords. The results highlight the relationship between AI and science education, underscoring the need for policies that promote continuous training and effective use of ICT. The research concludes that AI can personalize learning, automate assessments, and create interactive content, enhancing digital competencies in science education.